2014
DOI: 10.1002/phar.1468
|View full text |Cite
|
Sign up to set email alerts
|

Physician-Pharmacist Collaborative Management of Asthma in Primary Care

Abstract: Objective To determine if asthma control improves in patients who receive physician-pharmacist collaborative management (PPCM) during visits to primary care medical offices. Design Prospective pre-post study of patients who received the intervention in primary care offices for 9 months. The primary outcome was the sum of asthma-related emergency department (ED) visits and hospitalizations at 9 months before, 9 months during, and 9 months following the intervention. Events were analyzed using linear mixed eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
51
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(53 citation statements)
references
References 29 publications
2
51
0
Order By: Relevance
“…6,7 The value of MTM has been established by increasing medication adherence, improving clinical outcomes, and leading to potential economic benefits. 8–14 For example, the Asheville project has shown that asthma patients achieved and maintained improvements in lung function and had asthma-related cost savings in health care after receiving MTM services. 13 In another study, pharmacists in collaboration with physicians in providing MTM services that resulted in reduced hospitalizations and emergency room visits and improved patient quality of life among patients with asthma.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…6,7 The value of MTM has been established by increasing medication adherence, improving clinical outcomes, and leading to potential economic benefits. 8–14 For example, the Asheville project has shown that asthma patients achieved and maintained improvements in lung function and had asthma-related cost savings in health care after receiving MTM services. 13 In another study, pharmacists in collaboration with physicians in providing MTM services that resulted in reduced hospitalizations and emergency room visits and improved patient quality of life among patients with asthma.…”
Section: Introductionmentioning
confidence: 99%
“…13 In another study, pharmacists in collaboration with physicians in providing MTM services that resulted in reduced hospitalizations and emergency room visits and improved patient quality of life among patients with asthma. 14 …”
Section: Introductionmentioning
confidence: 99%
“…The primary outcome of the asthma arm in the usual care BP group was the sum of asthma-related emergency department (ED) visits and hospitalizations in three periods: 9 months before intervention, 9 months during, and 9 months after the intervention. Of the 126 patients in the asthma arm, the number of ED visits and/or hospitalizations decreased 30% during the intervention (p=0.052) and returned to preenrollment levels after the intervention was discontinued (p=0.83) [17].…”
Section: Resultsmentioning
confidence: 99%
“…To our knowledge none have evaluated barriers and facilitators in a large, randomized, multihealth system clinical trial. The results from both the BP and asthma interventions from the CAPTION Trial have recently been published [17,18]. Not only was the intervention shown to improve blood pressure control, it was also shown to be cost effective considering both cost of medications and pharmacist and physician time [19].…”
Section: Introductionmentioning
confidence: 99%
“…Face‐to‐face pharmacist interventions clearly increase patient adherence to asthma controller therapy . The effectiveness of pharmacy‐based education, counselling and monitoring of drug adherence to reduce hospitalisations and improve disease control has been demonstrated in several conditions, including asthma . Led by Australia, Finland and the Netherlands, there is currently a global movement to expand pharmacist's professional activities beyond drug dispensing and monitoring, towards acting as case managers coordinating asthma care .…”
Section: Introductionmentioning
confidence: 99%